PEREMPUAN DALAM DISKRIMINASI ETNIS DI INDONESIA (ANALISIS FILM SAPU TANGAN FANG YIN) - Prinisia Nurul Ikasari (Jurnal Komunikasi dan Kajian Media, 2017)
Ethnic Chinese are ethnic minorities in Indonesia since independence became a frightening thing for the Indonesian nation. This study aims to explain discrimination against ethnic Chinese in Indonesia through analysis in Sapu Tangan Fang Yin Movie. This research uses a qualitative approach through semiotic analysis Roland Barthes. The results of this study indicate the existence of symbolic violence in Sapu Tangan Fang Yin Movie, discrimination arises in the form of swearing, metaphor, and visual became a real discriminatory tool in the ethnic Chinese existence.